(untitled) (Revista de Artes Marciales Asiáticas, 2012)
A provisional bibliography about Asian martial arts periodicals published in Spain from 1961, first journal’s publication date, to 2009 is presented. Asian martial arts journals were just included for preparing this bibliography. Main public documentary centres as well as personal archives were visited for information searching and data mining. Analysis process was complex due to the scarce number of this kind of publications collected in public institutions. 66 periodicals were discovered and several useful elements were detailed for their description and documentary analysis (title, type of publication, period, frequency, issues, editor, place of publication, ISSN and a brief explanation of their editorial line). Despite its provisional character, this bibliography shows the great amount and variety of data contained in these periodicals, turning into a relevant resource for studying the martial arts’ history in Spain.